Mountain, Water, Rock, God : Understanding Kedarnath in the Twenty-First Century - Whitmore, Luke, 1973- (Book collections on Project MUSE., 2018)
"In Mountain, Water, Rock, God, Luke Whitmore situates the disastrous flooding that fell on the Hindu Himalayan shrine of Kedarnath in 2013 within a broader religious and ecological context. Whitmore explores the longer story of this powerful realm of the Hindu god Shiva through a holistic theoretical perspective that integrates phenomenological and systems-based approaches to the study of religion, pilgrimage, place, and ecology. He argues that close attention to places of religious significance offers a model for thinking through connections between ritual, narrative, climate destabilization, tourism, development, and disaster, and he shows how these critical components of human life in the twenty-first century intersect in the human experience of place"--Provided by publisher